The Benefits and Risks of Spraying Disinfectants in The Public Spaces During The Coronavirus Disease 2019 (Covid-19) Pandemic: A Literature Review Stud - Pramono, Pramono; Indasah, Indasah (Journal of Health Sciences, 2022)
Coronavirus Disease 2019 (COVID-19) spreads quickly through droplets from the patient’s nose or mouth, falls on objects around them, and becomes the transmission source for others. Therefore, the community prevents COVID-19 transmission by spraying disinfectants in the environment and using sanitary booths for humans despite not being recommended by the Indonesian government and WHO because it’s a health risk. This study analyzes the benefits and risks of spraying disinfectants in public spaces during the Coronavirus Disease 2019 pandemic. This study used six database sources: Pubmed ScienceDirect, ResearchGate, Google Scholar, Pusat Penelitian dan Pengembangan Upaya Kesehatan Masyarakat (Puslitbang Ukesmas), and Elsevier during 2016-2021, with inclusion and exclusion criteria selected by the authors on PRISMA flow diagram. There were 15 articles matching those criteria. Nine concluded that spraying disinfectants in the community could prevent the spread of COVID-19. In addition, it was efficient for surface objects and large areas. Furthermore, ≤ 200 ppm chlorine-based disinfectants and 15% alcohol-based were safe to use. Meanwhile, six articles revealed a risk of spraying disinfectants due to improper disinfectants mixing and spraying disinfectants on food and the body. In conclusion, spraying disinfectants in the community is safe for the eyes, respiratory tract, and skin of humans. It also can prevent the spread of Coronavirus Disease 2019 when the method, material, and usage are appropriate.